THE CONCEPT OF COGNITIVE METAPHOR - Cherkas , Nataliia (Collection of scientific papers «ΛΌГOΣ», 2024)
With the appearance of the work by J. Lakoff and M. Johnson "Metaphors We Live by", the term conceptual metaphor entered linguistic usage, which is seen in the process of understanding one concept or conceptual area in terms of another concept or conceptual area [1]. The essence of a metaphor, according to J. Lakoff, is the understanding of one thing through another. Most of our conceptual system is metaphorically structured, that is, most concepts can be partially understood through other concepts [1]. The theory formulated in the work cited above interprets metaphor as a device for understanding new conceptual spheres in terms of spheres that are closer to a person: cf. literal geometric use of the definition of high in the phrase a tall man, a tall tree and its metaphorical transfers to the sphere of mechanical (high speed), thermo- (high temperature) and electrical (high voltage) dynamics, ethics (high morality, high responsibility), aesthetics ( high art), law (high court), social relations (high post), labour activity (high skill), etc. There is also a reduction of various semantic relations to fairly elementary (primarily spatial) schemes. In other words, through metaphors, complex conceptual spheres – areas of sensory or social experience that cannot be observed directly, are compared with simpler or concretely observed spheres. At the same time, the conceptual domain is a set of knowledge, thematically separated from other sets of knowledge; it is a coherent space of conceptualization in relation to which semantic units can be characterized. Basic conceptual areas are three-dimensional space, smell, color, sensory perceptions, etc. A concept or conceptual complex of any degree of complexity can function as an abstract conceptual domain (such as a human body, the rules of chess, kinship relations) [2]. Thus, the establishment of similarity is possible not only between two specific concepts, but also between conceptual complexes. Various researchers emphasize the special importance of extralingual information in the processes of metaphor formation and interpretation (E. McCormack, 1990; Fillmore, 1983; van Dijk, 1998; Dijk, 1972; 1983; Lakoff, 1981; 1989; Lakoff, Johnson, 1990). They are also united by the following thesis: since our concepts organize our perception of reality, ways of behaving in the world, and features of the communicative system, and our conceptual system is mainly metaphorical, our thinking, experience, and behavior are largely conditioned by metaphor. Thus, metaphors structure our perception, thinking and activity. At the same time, as emphasized by J. Lakoff and M. Johnson [3], the essence of metaphor can be considered as understanding and experiencing one kind of phenomena in terms of phenomena of another kind.